2018
DOI: 10.3389/fnins.2018.00103
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Music Education on Executive Functions in Primary School Children

Abstract: Background: Research on the effects of music education on cognitive abilities has generated increasing interest across the scientific community. Nonetheless, longitudinal studies investigating the effects of structured music education on cognitive sub-functions are still rare. Prime candidates for investigating a relationship between academic achievement and music education appear to be executive functions such as planning, working memory, and inhibition.Methods: One hundred and forty-seven primary school chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
155
2
22

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(195 citation statements)
references
References 47 publications
(93 reference statements)
16
155
2
22
Order By: Relevance
“…In order to appraise abstract reasoning, we applied the Matrices subtest of the WISC-IV (Wechsler, 2003). Since musical phrases develop over time according to musical grammar, like language (Patel, 2012), we consider that some abstract thinking is involved in producing and processing music (Jaschke, Honing, & Scherder, 2018b). The test consists of different sheets with series of three images (e.g.…”
Section: Matrix Reasoningmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to appraise abstract reasoning, we applied the Matrices subtest of the WISC-IV (Wechsler, 2003). Since musical phrases develop over time according to musical grammar, like language (Patel, 2012), we consider that some abstract thinking is involved in producing and processing music (Jaschke, Honing, & Scherder, 2018b). The test consists of different sheets with series of three images (e.g.…”
Section: Matrix Reasoningmentioning
confidence: 99%
“…The absence of significant effects for the for the three subtests of the Rey Auditory Verbal Learning Test may surprise, as increase of verbal memory and other language functions is reported often as an effect of musical training (Ho, Cheung, & Chan, 2003;Jaschke et al, 2018b;Roden et al, 2012). But we should acknowledge that 1) the control group was also musically trained, and sensitization to music did show a trend for verbal IQ (Jaschke et al, 2018a), 2) children in which verbal advantages were observed started musical training at a younger age on average than the groups tested in the current experiment (Ho et al, 2003;Jaschke et al, 2018b;Roden et al, 2012) and 3) that we did find a marginal positive effect of verbal learning in the OC group as compared to the Control Group, that may have failed to reach statistical significance following lack of statistical power as our groups are of medium size.…”
Section: Far Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…In the Netherlands, 147 school children were followed for 2.5 years while pursuing in-school art projects (Jaschke et al, 2018). They were randomized into four groups: two music intervention groups, one visual arts group, and passive control group.…”
Section: Studies In Community Settingsmentioning
confidence: 99%
“…Al realizar una pequeña investigación en la documentación científica actual, es fácil encontrar estudios donde la investigación en psicología y neurociencia comienza a preguntarse qué ocurre con estos niños y adolescentes que estudian música (Habibi, Damasio, Ilari, Sachs y Damasio, 2018;Habibi y cols., 2017;Moreno y cols., 2008). Los resultados, en su mayor parte positivos, demuestran que la formación musical en niños de edad escolar se asocia con una mejora de habilidades verbales y razonamiento general (Herrero y Carriedo, 2018;Jaschke, Honing y Scherder, 2018;Roden, Kreutz y Bongard, 2012). También es cierto que la ciencia avanza despacio y aún es difícil saber a qué nivel se producen estos cambios y la causa de los mismos (Miendlarzewska y cols., 2014).…”
unclassified